2019
DOI: 10.3390/ijerph16142545
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment on Benzene Exposure among Gasoline Station Workers

Abstract: Benzene is a human carcinogen presented in gasoline (1% by volume). It is also found in vehicle exhaust. The aim of this study was to assess the health risk of inhalation exposure to benzene among gasoline station workers. The ambient benzene concentration was measured by personal sampling from 150 gasoline station workers (137 fueling workers and 13 cashiers). Additional data of working characteristics were collected by interviews and on-site observations. All workers were non-smokers and passive smoking was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 16 publications
4
43
1
1
Order By: Relevance
“…A significant correlation was found between fire risk levels in FHZ‐II and a station's location. That is consistent with the previous report of higher health risk among workers at urban and suburban gasoline stations compared to rural stations 20 . Gasoline stations in suburban zones were located along the main highway connecting Bangkok, the capital city to the countries of the Mekong sub‐region, relating to our previous study which showed that a high benzene concentration in the air correlated with the daily amount of gasoline sold 21 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A significant correlation was found between fire risk levels in FHZ‐II and a station's location. That is consistent with the previous report of higher health risk among workers at urban and suburban gasoline stations compared to rural stations 20 . Gasoline stations in suburban zones were located along the main highway connecting Bangkok, the capital city to the countries of the Mekong sub‐region, relating to our previous study which showed that a high benzene concentration in the air correlated with the daily amount of gasoline sold 21 .…”
Section: Discussionsupporting
confidence: 92%
“…For example, with regard to the health risk from air benzene exposure, it was shown that 15.3% of gasoline station workers were at a higher than acceptable level of risk, 5 even though the benzene concentration was not higher than the standard occupational exposure limit (OEL-TWA; <0.1 ppm) set by NIOSH. 6 According to tt-muconic acid (tt-MA) biomarker monitoring, 36.7% of workers were at a higher than acceptable risk level, 7 although it had been found that only 12% of those workers had a detected concentration of tt-MA higher than the biological exposure index (>500 microgram per gram of creatinine), recommended by ACGIH. 8 This situation not only has impacts on health, but it might also cause a fire risk at gasoline stations.…”
Section: Introductionmentioning
confidence: 99%
“…This is a condition that the gasoline workers should be aware of protecting themselves against even though the ambient benzene concentration was below the permissible exposure level. The previous study also showed that workers could exceed acceptable health risk levels with chronic exposure to benzene at the concentration of 10% of the permissible exposure level set by ACGIH [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The univariate analysis showed that workers who did not wash their hands before eating had a significantly higher risk of benzene exposure via the oral route than the workers that washed their hands. Our previous study suggested that gasoline station workers exposed to benzene were potentially exposed via the oral route while eating at work [36]. Furthermore, another significant risk factor was the absence of job training.…”
Section: Discussionmentioning
confidence: 99%
“…16,19 Chronic occupational exposure to PPF constituent is primarily detrimental to human health, [20][21][22][23] which can be further exacerbated by the absence of enforceable occupational safety regulation, inadequate personnel safety equipment, and unsafe work conditions. [24][25][26][27][28] Besides, PDS attendants are responsible for unloading petroleum products from supply tankers into PDS underground reservoirs and take daily stock of dispensed petroleum products from PDS reservoirs. 29 PDS attendants chronically exposed to PPF fractions, and their by-products, mainly by inhalation of volatile fractions 30 and dermal contact during a regular workday (8-10 hours).…”
Section: Introductionmentioning
confidence: 99%